Islamic Financial Behavior: The Influence of Lifestyle, Financial Learning, and Family Financial Education on the Sharia Financial Literacy of Muslim Students at Lambung Mangkurat University - Azma, Aulia Rahmiyatul; Misran, Alfian; Nordiansyah, Muhammad (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This study aims to analyze the influence of lifestyle, financial learning, and family financial education on the Sharia financial literacy of Muslim students at Lambung Mangkurat University. Using a quantitative approach, data were collected from 85 undergraduate accounting students through questionnaires and analyzed using multiple linear regression. The results show that lifestyle significantly affects Sharia financial literacy (t = 2.816; p = 0.006), financial learning also has a significant effect (t = 2.028; p = 0.046), and family financial education demonstrates a significant influence (t = 2.243; p = 0.028). Simultaneously, the three variables jointly affect financial literacy with a significance value of F = 19.294 (p = 0.000). Among these factors, lifestyle exerts the strongest influence, indicating that prudent, value-based, and moderate behavior shapes ethical financial decision-making. These findings support the Theory of Planned Behavior (TPB), where lifestyle represents attitude toward behavior, and financial learning and family education relate to subjective norms and perceived behavioral control. Theoretically, the research extends the behavioral finance model by integrating Islamic ethical dimensions rooted in fiqh al-muʿāmalah and maqāṣid al-sharī‘ah, emphasizing the preservation and responsible use of wealth (ḥifẓ al-māl). Practically, the study provides insights for universities, regulators, and families to enhance Islamic financial education that promotes not only financial knowledge but also ethical and socially responsible behavior.